American Association for the Surgery of Trauma Prevention Committee topical update: Impact of community violence exposure, intimate partner violence, hospital-based violence intervention, building community coalitions and injury prevention program evaluation. Issue 2 (August 2019) - Rosenblatt, Michael S.; Joseph, Kimberly T.; Dechert, Tracey; Duncan, Thomas K.; Joseph, D'Andrea K.; Stewart, Ronald M.; Cooper, Zara R.
Abstract : ABSTRACT: An effective injury prevention program is an important component of a successful trauma system. Maintaining support for a hospital-based injury prevention program is challenging, given competing institutional and trauma program priorities and limited resources. In light of those pressures, the American College of Surgeons Committee on Trauma mandates that trauma centers demonstrate financial support for an injury prevention program as part of the verification process, recognizing that hospital administrators might see such support as discretionary and ripe as a target for expense reduction efforts. This Topical Update from the American Association for the Surgery of Trauma Injury Prevention Committee focuses on strategies to be more effective with the limited resources that are allocated to hospital-based injury prevention programs. First, this review tackles two of the many social determinates of violence, including activities aimed at mitigating the impact of both community violence exposure and intimate partner/domestic violence. Developing or participating in coalitions for injury prevention, both in general with any injury prevention initiative, and specifically while developing a hospital-based violence intervention program, efficiently extends the hospital's efforts by gaining access to expertise, resources, and influence over the target population that the hospital might otherwise have difficulty impacting. Finally, the importance of systematic program evaluation is explored. In an era of dwindling resources for injury prevention, both at the national level and the institutional level, it is important to measure the effectiveness of injury prevention efforts on the target population, and when necessary, make changes to programs to both improve their effectiveness and to assist organizations in making wise choices in the use of their limited resources.